Clinical outcome of eplerenone in the management of acute central serous chorioretinopathy - Pramod Kumar Sharma; Bhagyashree Padhan; Ipsita Khuntia; Madhumita Naik; Biswambara Satpathy (Oman Journal of Ophthalmology)
OBJECTIVES: To evaluate the clinical outcomes of eplerenone in the management of acute central serous chorioretinopathy (CSCR). MATERIALS AND METHODS: This case–control study involved 52 eyes of 52 cases of acute CSCR divided between treatment (26) and control (26) groups. Cases in the treatment group were managed by tablet eplerenone 50 mg/d. During the scheduled visits, serum electrolytes and an ophthalmic evaluation, including optical coherence tomography, were conducted. The control group was subject to observation and a similar follow-up. The Statistical Programme for Social Sciences, version 23 was used for statistical tests. RESULTS: The mean age in the treatment and control group was 39.15 ± 12.1 years and 36.1 ± 8.09 years, respectively. In the treatment group, 46.15% of right eyes and 53.8% of left eyes, and in the control group, 61.5% of right eyes and 38.5% of left eyes were evaluated. Visual acuity improved to 6/6 in 96.2% of treated cases and 19.2% of controls in the 2nd month of follow-up. Subretinal fluid resolved completely in 61.52% of treated cases and 38.46% of controls at 12-week follow-up. No adverse events were reported, and by the 12th week of follow-up, the mean serum K+ was 4.80 ± 0.157 mEq/L. CONCLUSION: Acute CSCR cases managed with oral eplerenone can attain faster resolution with significant functional improvement. Eplerenone may serve as a first-line therapeutic option for acute CSCR with a better safety profile.